Alterität: Zur Entwicklung einer Denkfigur bei Alfred Döblin - Christine Maillard (Recherches Germaniques)
This brief introduction to this dossier, which is dedicated to the experience and construction of otherness in Döblin’s life and work, starts with the observation that while the relationship to cultural otherness and to non-European cultures has long been documented in research on his literary work, the question of the Other, although strongly present, has never been fundamentally questioned in works with philosophical and religious interest. Through an examination of Döblin’s philosophical work, “Unser Dasein” (1933), and the religious dialogue “Der unsterbliche Mensch” (1946), this paper will show that the figure of the Other is central to Döblin’s thinking in its psychological, ethical, and mystical dimensions, and is constitutive of his modernity.